1972
DOI: 10.1128/jb.109.3.1034-1046.1972
|View full text |Cite
|
Sign up to set email alerts
|

Altered Phospholipid Metabolism in a Sodium-Sensitive Mutant of Escherichia coli

Abstract: A mutant of Escherichia coli has been isolated, the growth of which is inhibited by low concentrations (1 mM) of NaCl. High levels of magnesium, calcium, or strontium in the medium permit growth in the presence of sodium. The metal content of the inhibited mutant is normal, but the strain is unable to tolerate levels of sodium to which the wild type is indifferent. Immediately after the addition of sodium to cultures of the mutant, rates of synthesis of protein, ribonucleic acid, deoxyribonucleic acid, and tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 39 publications
4
11
0
Order By: Relevance
“…Rampini et al (285) observed that inhibition of energy generation, which blocks the formation of CDP-diglyceride, does not inhibit the synthesis of cardiolipin in vivo. Since phos-phatidylglycerol levels dropped as cardiolipin accumulated, these workers proposed the following reaction: 2 phosphatidylglycerol,-cardiolipin + glycerol (2) This mechanism was also compatible with the work of Lusk and Kennedy (194), who demonstrated that free glycerol was released from phosphatidylglycerol in radiochemical labeling experiments with living cells.…”
Section: Enzymology Of Phospholipid Synthesissupporting
confidence: 70%
See 2 more Smart Citations
“…Rampini et al (285) observed that inhibition of energy generation, which blocks the formation of CDP-diglyceride, does not inhibit the synthesis of cardiolipin in vivo. Since phos-phatidylglycerol levels dropped as cardiolipin accumulated, these workers proposed the following reaction: 2 phosphatidylglycerol,-cardiolipin + glycerol (2) This mechanism was also compatible with the work of Lusk and Kennedy (194), who demonstrated that free glycerol was released from phosphatidylglycerol in radiochemical labeling experiments with living cells.…”
Section: Enzymology Of Phospholipid Synthesissupporting
confidence: 70%
“…The changes in the lipid composition of mutants in thepss gene resemble those of a sodiumsensitive mutant described earlier by Lusk and Kennedy (194). A careful study of this mutant failed to reveal any defect in phosphatidylserine synthetase activity in vitro (194). A similar alteration of lipid composition is observed during infection of E. coli with certain amber mutants of bacteriophage fl (384).…”
Section: Mutants In Phosphatidylethanolamine Synthesismentioning
confidence: 59%
See 1 more Smart Citation
“…However, the physiological origin of the thermal stability of the membranes of these cells remains an interesting open question. Some possible explanations are the differences in their membrane composition (1,10,13,(29)(30)(31)(32)(33), stronger intermolecular interactions in cell envelope (34)(35)(36), and/or the detoxification of oxygen radicals by Mg 2þ ions (8,(37)(38)(39)(40)(41)(42), as discussed in detail in the Supporting Material. Finally, 5) we observed that k f pulse > k f ramp at otherwise similar conditions (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of CL synthesis in OS2101 after the elevation of the culture temperature suggested the existence of regulatory mechanisms in the biosynthesis and metabolism of phospholipids. A decrease in PE and increase in CL have been simultaneously observed in a sodium-sensitive E. coli mutant (18), phenethyl alcohol-treated cells (21), and an envC division mutant (19). A simple increase in PG turnover to CL is usually seen in the transition from the exponential to the stationary phase of growth (6).…”
Section: Discussionmentioning
confidence: 99%